Sampled-data-based dissipative control of T-S fuzzy systems - Zeng, H.; Teo, Kok Lay; He, Y.; Wang, W. (Elsevier, 2019)
This paper investigates the problem of sampled-data-based dissipative control of Takagi–Sugeno (T-S) fuzzy systems. The sampling period is assumed to be varying within an interval. By making full use of realistic information about the whole sampling interval, we propose a novel complete sampling-interval-dependent looped function, which depends not only on the interval from x(t) to x(tk) but also on the interval from x(t) to x(tk+1). Based on this function, a sufficient condition is established, ensuring the considered system strictly (Q,S,R)-?-dissipative. Furthermore, a approach to design desired sampled-data controllers is proposed. It is applied to solve the problems of a truck-trailer and an inverted pendulum. From the results obtained, we see that this approach is highly effective.